Gerak Tari Janger sebagai Media Pengembangan Kepercayaan Diri Anak Usia Dini - Diah Maharani, Ni Putu; Wedayanthi, Luh Made Dwi (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aimed to enhance the self-confidence of early childhood learners through the Janger Dance Movement, used as an art- and culture-based learning medium. The program was implemented at TK Prawidya Dharma in Demulih Village, Bangli, involving children aged 5–6 years and their teachers. A qualitative descriptive method was applied using the Participatory Action Learning System (PALS) approach, which emphasizes active engagement, reflection, and participatory learning. The results showed a significant improvement in the children's self-confidence, evidenced by their increased willingness to perform in public, improved social interaction, and more expressive emotional behavior. Teachers also benefited from enhanced pedagogical competence, particularly in integrating cultural and artistic elements into meaningful classroom practices. The Janger Dance Movement proved to be an effective pedagogical strategy for fostering self-confidence, independence, and social development in early childhood education. This approach not only helped children build self-esteem but also encouraged them to engage in creative expression, while allowing teachers to gain valuable experience in incorporating cultural arts into their teaching practices.